RIGHTS AND FREEDOMS OF A PERSONE AND A CITIZEN IN THE OCCUPIED TERRITORIES - Piskun, Ivan; Kurtmollayev , Asan (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
Purpose of the article. To analyze the legal status of the temporarily occupied territories of Ukraine and its impact on the observance of human and civil rights and freedoms. Investigate the main types of violations of human and civil rights and freedoms in the temporarily occupied territories. Research methods: the work uses a set of general scientific and special research methods. An important method of research was the dialectical method of cognition, through which the qualitative characteristics of the phenomenon under study were identified and determined. Results: the temporarily occupied territories of Ukraine are an integral part of its territory and are subject to the Constitution and legislation of Ukraine. In the occupied territories there is a systematic and massive violation of the rights and freedoms of man and citizen. The international community must take stronger measures to stop human rights violations in the occupied territories. Discussion of the topic: systematic and gross violation of human rights and freedoms in the temporarily occupied territories of Ukraine is one of the most acute problems of the modern world. These violations constitute a gross attack on the basic principles of international law and constitute a threat to peace and security in Europe. The international community should take all possible measures to stop these violations and protect human rights and freedoms in the occupied territories.